Innovating urinary catheter design: An introduction to the engineering challenge. (January 2019) - Murphy, Cathy
Every day, people around the world rely on intermittent and indwelling urinary catheters to manage bladder dysfunction, but the potential or actual harm caused by these devices is well-recognised. Current catheter designs can cause urinary tract infection and septicaemia, bladder and urethral trauma and indwelling devices frequently become blocked. Furthermore, the devices can severely disrupt users' lives, limiting their daily activities and can be costly to manage for healthcare providers. Despite this, little significant design innovation has taken place in the last 80 years. In this article current catheter designs and their limitations are reviewed, common catheter-associated problems are outlined and areas of design ripe for improvement proposed. The potential to relieve the individual and economic burden of catheter use is high.